IMPACT OF INFLATION ON INFRASTRUCTURAL INVESTMENT IN NIGERIA - Nnenna, Onyeka Virginia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Inflation affects both the private and government sectors as well as individuals. It triggers prices if not properly managed and reduces the zeal for investment; an investment is an indispensable aspect of any economy. It is therefore against the effect of inflation on the economy that our paper examined the impact of inflation on infrastructural investment in Nigeria. Our result showed that the impact of inflation rate on infrastructural investment was negative and significant in Nigeria. We therefore, recommend that government should stick to prudent economic policies avoid excessive money printing which inflation targeting would achieved via price stabilization and also promote investment climate in Nigeria.